Comparison of the Optical Quality between Small Incision Lenticule Extraction and Femtosecond Laser LASIK - Ying Jin; Yan Wang; Lulu Xu; Tong Zuo; Hua Li; Rui Dou; Jiamei Zhang (Journal of Ophthalmology)
Purpose. To investigate the visual quality after SMILE and Femto-LASIK. Methods. About 123 eyes from 63 patients were enrolled in this study. The parameters were measured preoperatively and 1 week, 1 month, and 3 months postoperatively using Sirius System. Results. The MTF curve increase slightly from low to high frequency at 3 mm and 6 mm pupil diameter after SMILE surgery (P<0.05) during the follow-up time comparing with the preoperative values. And the SR has a significant increase at various pupil diameters as well (P<0.05). However, there was little increase for MTF at intermediate to high frequency at 3 mm pupil diameter after Femto-LASIK procedure (P<0.05). And the SR had only significant increase at 3 mm pupil diameter. Between SMILE and Femto-LASIK, there was no statistic difference both in MTF and SR (P>0.05) at 3 mm pupil diameter at vertical and horizontal meridian. However, significant difference was found in MTF at low to mediate frequency at 6 mm pupil diameter at vertical meridian at 1 week postoperatively (P<0.05). Conclusions. Both SMILE and Femto-LASIK show a great improvement in optical quality at small diameter. It was found that SMILE shows better optical quality than Femto-LASIK at larger pupil diameter, which might be good for the night vision.